2015
DOI: 10.1111/aphw.12058
|View full text |Cite
|
Sign up to set email alerts
|

Are People Living in Walkable Areas Healthier and More Satisfied with Life?

Abstract: Are people who live in more walkable areas healthier and more satisfied with life? This study investigates that question by using the 2005 Behavioral Risk Factors Surveillance System (BRFSS) survey, the largest telephone survey on health in the US (302,841 respondents from 989 metropolitan and micropolitan statistical areas [MSA]; 177,524 respondents from 703 MSAs had complete data). Using multilevel random coefficient modeling, we found that people living in walkable areas reported being generally healthier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…However, it can be argued that neither study has adopted a real multilevel perspective, as both have matched environment‐level data to individual data – with the potential of committing an ecological fallacy (Robinson, ). As environmental features such as walkability have a direct influence on health and health behaviours (e.g., Oishi, Saeki, & Axt, ), it is likely that people living in the same area are more similar to each other than people in different areas: Living in a resource‐rich environment should make the self‐regulation of health behaviour (e.g., following through on intentions) easier than living in a resource‐poor environment. This suggests that we need to take the clustering of participants in ecological entities such as neighbourhoods or cities into account when examining such cross‐level interactions.…”
Section: Environment‐level Facets Of Ses – Need For a Multilevel Resementioning
confidence: 99%
“…However, it can be argued that neither study has adopted a real multilevel perspective, as both have matched environment‐level data to individual data – with the potential of committing an ecological fallacy (Robinson, ). As environmental features such as walkability have a direct influence on health and health behaviours (e.g., Oishi, Saeki, & Axt, ), it is likely that people living in the same area are more similar to each other than people in different areas: Living in a resource‐rich environment should make the self‐regulation of health behaviour (e.g., following through on intentions) easier than living in a resource‐poor environment. This suggests that we need to take the clustering of participants in ecological entities such as neighbourhoods or cities into account when examining such cross‐level interactions.…”
Section: Environment‐level Facets Of Ses – Need For a Multilevel Resementioning
confidence: 99%
“…Few studies have investigated neighbourhood walkability and subjective measures of well-being. These associations were examined in recent analyses of the US Behavioral Risk Factors Surveillance Survey, which found that those who lived in more walkable neighbourhoods were more likely to report improved overall general health, but were less satisfied with life [11]. Importantly, cross-sectional and quasi-longitudinal analyses of movers and non-movers that were able to account for neighbourhood preferences and individual attitudes found that neighbourhood design characteristics are associated with physical activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of walkability has been gaining increased attention by scholars, city authorities, social movements and initiatives, and urban planners in the last few decades. A walkable built environment has numerous positive effects on residents' well-being: it increases the number of walking trips (Cerin et al, 2007;Manaugh and El-Geneidy, 2011;Weinberger and Sweet, 2012) and thus enhances physical activity and health (Oishi et al, 2015;Rundle et al, 2016;Saelens et al, 2003); enhances life satisfaction (Cao, 2016;Besta, 2016, 2014); the level of social capital (Rogers et al, 2011); and residents' creativity (Oppezzo and Schwartz, 2014). Among many walking needs, which range from feasibility to pleasurability (Alfonzo, 2005), good spatial accessibility from origins to destinations is found to be one of the most important, and it has been shown to influence the decision to walk over other transport modes (Boisjoly et al, 2018;Frank and Engelke, 2005;Giles-Corti et al, 2005;Giles-Corti and Donovan, 2002;Greenwald and Boarnet, 2001;Lund, 2003;Moudon et al, 2006;Owen et al, 2004;Reyer et al, 2014;Shriver, 1997).…”
Section: Theoretical Backgroundmentioning
confidence: 99%